2021
DOI: 10.1097/cji.0000000000000360
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Baseline Corticosteroids on Immunotherapy Efficacy in Patients With Advanced Melanoma

Abstract: This is a 2-center, retrospective study which aimed to evaluate the effect of baseline corticosteroid use on immunotherapy efficacy in patients with advanced melanoma. We included all patients with advanced unresectable and metastatic melanoma on single-agent programmed cell death protein 1 (PD-1) inhibitors at the Cancer Centre of Southeastern Ontario and London Regional Cancer Program. We defined baseline corticosteroid use as prednisone-equivalent of ≥ 10 mg within 30 days of immunotherapy initiation. Our s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
(92 reference statements)
0
11
0
Order By: Relevance
“…Whether systemic corticosteroids, due to their immunosuppressive effect, might or not ICI when administered right before or during treatment is another matter of debate. Several studies led to the conclusion that avoiding or delaying the use of corticosteroids may result in maximizing the potential treatment benefits of immunotherapy [12][13][14][15][16]. However, other evidences highlight that corticosteroids have no detrimental effect on immunotherapy and high doses of steroids might reflect poorer basal conditions (e.g., active brain metastases, concurrent diseases, larger tumor volume), ultimately responsible for the scarce outcomes with ICI [17,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether systemic corticosteroids, due to their immunosuppressive effect, might or not ICI when administered right before or during treatment is another matter of debate. Several studies led to the conclusion that avoiding or delaying the use of corticosteroids may result in maximizing the potential treatment benefits of immunotherapy [12][13][14][15][16]. However, other evidences highlight that corticosteroids have no detrimental effect on immunotherapy and high doses of steroids might reflect poorer basal conditions (e.g., active brain metastases, concurrent diseases, larger tumor volume), ultimately responsible for the scarce outcomes with ICI [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the optimal metastatic therapeutic setting (earlier or further lines), the efficacy in immunepretreated patients, the effects of exposure to immediately previous or concurrent radiotherapy (RT), and the optimal duration of treatment remain questions unanswered. To note, the impact of systemic corticosteroids and exposure to antibiotic (ATB) therapy on response to ICI are another major concern, with only few and/or conflicting data being published so far [9][10][11][12][13][14][15][16][17][18]. Finally, easy-to-detect and relatively low cost prognostic predictors able to stratify patients for either ICI clinical trial inclusion or better tailoring of the treatment strategy are urgently needed and the LIPI score, based on a relative neutrophil count and LDH is a promising one, which merits further validation in a pan-cancer setting [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…This is an important potential prognosticating variable, given that systemic corticosteroid use has been previously correlated with immunosuppression [ 16 , 17 ], further drawing concerns of impairing ICI efficacy in advanced cancer patients. Multiple studies reported early corticosteroid use prior to ICI may be linked with decreased efficacy in various advanced cancer settings [ 18–22 ], particularly if indicated for cancer symptom relief [ 20 ], as well as higher dose [ 21 ] and prolonged use of corticosteroid [ 22 ]. Nevertheless, these studies evaluated single ICI rather than dual ICI.…”
Section: Discussionmentioning
confidence: 99%
“…They found that receiving corticosteroid therapy had no significant relationship with the patients’ overall survival (OS) ( 11 ). However, there are some studies suggesting that a high baseline prednisone dose is associated with poor survival ( 12 ). They speculated that the use of steroid hormones before ICI treatment may affect the activation of primitive T cells, thereby affecting the efficacy of immunotherapy, while the use of steroid hormones during treatment would only affect the activated T cells, and this effect cannot reduce the overall efficacy of immunotherapy ( 12 ).…”
Section: Discussionmentioning
confidence: 99%